West Indian Manatees Use Partial Migration to Expand Their Geographic Range Into the Northern Gulf of Mexico - Cloyed, Carl S.; Hieb, Elizabeth E.; DaCosta, Kayla; Ross, Monica; Carmichael, Ruth H. (Frontiers in Marine Science, 2021)
Partial migration provides a mechanism for species to shift their geographic ranges into new, environmentally favorable regions but has been poorly studied as a means to alleviate effects of climate change. Populations at the edge of their geographic range are ideal to investigate how migratory behaviors may enable range expansion as adjacent areas become more climatically favorable. We determined the contribution of partial migration to the range expansion of West Indian manatees (Trichechus manatus) using GPS data from tagged individuals that migrated between the northern Gulf of Mexico (nGoM) and primary habitat in peninsular Florida. Most of these manatees migrated to the nGoM annually and exhibited high site fidelity among years. Many individuals spent cumulatively more time in the nGoM than in peninsular Florida, indicating the nGoM is a regular part of their geographic range, and they returned to peninsular Florida to meet temperature-related physiological needs for survival. Autumn migrations most frequently terminated at Crystal River, Florida, and manatees that commenced migration late in the season stopped less frequently and had more directed movements. Spring migrations most frequently terminated at Mobile Bay, Alabama, and several manatees quickly and directly migrated from Florida to nGoM stopover sites. Migrations ranged from 10 – 133 days in length, and variation in duration was primarily driven by use of stopover sites and directedness of travel. These data confirm partial migration as an important component of manatee migratory behavior that has already enabled range shifts for manatees on the U.S.A. Gulf of Mexico coast and has potential to facilitate future responses to climate change. As the most common type of migration across the animal kingdom, partial migration may provide a global mechanism for a diverse variety of species to resist the range limiting effects of climate change.